Exploring Cholinergic Compounds for Peripheral Neuropathic Pain Management: A Comprehensive Scoping Review of Rodent Model Studies - Edouard Montigné; David Balayssac (MDPI AG, 2023)
Neuropathic pain affects about 7-8% of the population, and its management still poses challenges with unmet needs. Over the past decades, researchers have explored the cholinergic system (muscarinic and nicotinic acetylcholine receptors: mAChR and nAChR) and compounds targeting these receptors as potential analgesics for neuropathic pain management. This scoping review aims to provide an overview of studies on peripheral neuropathic pain (PNP) in rodent models, exploring compounds targeting cholinergic neurotransmission. The inclusion criteria were original articles on PNP in rodent models that explored the use of compounds directly targeting cholinergic neurotransmission and reported results of nociceptive behavioral assays. The literature search was performed in the PubMed and Web of Science databases (1 January 2000-22 April 2023). The selection process yielded 82 publications, encompassing 62 compounds. The most studied compounds were agonists of α4β2 nAChR and α7 nAChR, and antagonists of α9/α10 nAChR, along with those increasing acetylcholine and targeting mAChRs. Studies mainly reported antinociceptive effects in traumatic PNP models, and to a lesser extent, chemotherapy-induced neuropathy or diabetic models. These preclinical studies underscore the considerable potential of cholinergic compounds in the management of PNP, warranting the initiation of clinical trials.